Pedagogical Challenges in Developing Critical and Logical Thinking in the Education System (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The 21st century demands a modern and dynamic education system that prioritizes the development of students’ cognitive, analytical, and decision-making abilities. This paper explores the importance of critical and logical thinking in educational contexts and analyzes pedagogical challenges that hinder their effective integration. It provides evidence-based recommendations and visual tools to guide the modernization of teaching practices.